2004
DOI: 10.1111/j.1365-3040.2004.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous fluxes of peroxyacetyl nitrate (PAN) into plant leaves

Abstract: Peroxyactyl nitrate (PAN) is the most abundant of the gaseous organic nitrates produced from the photochemistry of hydrocarbons and NO x (i.e. ozone and smog production). PAN is known to be toxic to plants and also as a reservoir for the transport nitrogen dioxide in the troposphere. Here, the effect of vegetation on PAN deposition was investigated in four plant species by measuring leaf fluxes of PAN in a dynamic leaf chamber using atmospheric PAN fumigations between 0.7 and 18 nmol mol ---

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…The leaf uptake of the organic form of nitrogen peroxyacetyl nitrate (CH 3 C(O)O 2 NO 2 ; PAN) has also been described (Okano et al 1990;Sparks et al 2003;Teklemariam and Sparks 2004). These authors suggest the assimilatory pathway after incorporation into the leaf apoplast would mirror that for NO 2 .…”
Section: Once In the Apoplast Nhmentioning
confidence: 98%
See 1 more Smart Citation
“…The leaf uptake of the organic form of nitrogen peroxyacetyl nitrate (CH 3 C(O)O 2 NO 2 ; PAN) has also been described (Okano et al 1990;Sparks et al 2003;Teklemariam and Sparks 2004). These authors suggest the assimilatory pathway after incorporation into the leaf apoplast would mirror that for NO 2 .…”
Section: Once In the Apoplast Nhmentioning
confidence: 98%
“…Currently, laboratory and field measurements have generated leaf-area specific flux rates for NO (e.g., Hereid and Monson 2001;Teklemariam and Sparks 2006), NO 2 (e.g., Thoene et al 1996;Weber and Rennenberg 1996;Gessler et al 2000Gessler et al , 2002Sparks et al 2001;Eller and Sparks 2006), NH 3 (e.g., Fangmeier et al 1994;Hanstein et al 1999;Ashraf et al 2003;Castro et al 2006), PAN (e.g., Sparks et al 2003;Teklemariam and Sparks 2004), and HONO (e.g., Schimang et al 2006). Direct estimates of leaf uptake of HNO 3 and ionic and particulate forms of NO 3 -and NH 4 ?…”
Section: Measurements At Different Levels Of Integrationmentioning
confidence: 99%
“…Total peroxy acyl and peroxy nitrates ( PNs, compounds with the formula RO 2 NO 2 (peroxy nitrates) or RC(O)O 2 NO 2 (peroxy acyl nitrates)) and ANs may include hydroxyl substituted species that are highly soluble in water, and are thus likely to strongly interact with the biosphere. Leaf-scale studies demonstrated that plants can directly uptake peroxyacetyl nitrate (PAN), demonstrating a mechanism for dry deposition of PAN (Sparks et al, 2003;Teklemariam and Sparks, 2004). Laboratory measurements have demonstrated uptake of PAN by an alfalfa canopy occurs with a deposition velocity of 0.75 cm s −1 (Hill, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Sparks (2009) pointed out that direct foliar uptake of atmospheric reactive nitrogen to biota could be a major source of global N input to ecosystems. Teklemariam and Sparks (2004) estimated as much as 20 % of regional dry deposition of N occurs via foliar uptake of PAN and that this addition could serve to enhance productivity (Teklemariam and Sparks, 2004). To the extent that stomatal processes dominate, PN deposition will occur according to spatial and temporal patterns that are different from HNO 3 , as HNO 3 deposition is thought to be controlled only by turbulent transport to surfaces and, as a result, PN deposition could be an even larger percentage of the total in some locations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, peroxynitrates are temporary reservoirs of NO x (≡ NO + NO 2 ) affecting regional and global tropospheric ozone formation (Hudman et al, 2004;Zhang et al, 2008;Parrish et al, 2009;Fiore et al, 2011) by sequestering NO x at the source and then releasing it in downwind rural and remote regions. PNs may also have a significant influence on climate via their effects on available nitrogen and thus ecosystem productivity (Bytnerowicz and Fenn, 1996;Goulding et al, 1998;Sparks et al, 2003;Teklemariam and Sparks, 2004;Sparks, 2009) and via their phytotoxicity and thus ecosystem health (Okano et al, 1990;Goulding et al, 1998). Recent research has brought attention to new mechanisms by which peroxynitrates might participate in linking the atmospheric and biospheric N cycles (Townsend et al, 1996;Holland et al, 1997;Teklemariam and Sparks, 2004;Sparks, 2009).…”
Section: Introductionmentioning
confidence: 99%